Geopolymer Mortars from Tuff Waste: A Circular Approach - Muradyan, Nelli; Arzumanyan, Arusyak; Kalantaryan, Marine; Khachatryan, Kristina; Zendri, Elisabetta; Arzumanyan, Avetik (Salehan Institute of Higher Education, 2025)
This study explores the potential use of volcanic tuff mining waste in geopolymer mortar formulations, aiming to enhance recycling and promote sustainable construction. Two filler-to-binder ratios (70/30 and 65/35) were developed using a geopolymer binder composed of tuff waste, dolomite powder, and sodium silicate. The mortars were subjected to heat treatments at 200, 350, 500, and 650°C for 8.5 hours. Compared to natural tuff (reference sample), water absorption decreased from 16.8% to 7.7%, with the lowest absorption observed in the 65/35 composition. Flexural strengths increased by 0.97% to 117.1%, and compressive strengths improved by 17.8% to 97.1%, reaching their maximum at 500°C; at 650°C, strengths declined due to water evaporation, shrinkage, and microcrack formation. Softening coefficients increased by over 10%, indicating enhanced resistance to water-induced softening. The study demonstrates that incorporating dolomite powder improves water resistance, while tuff waste serves effectively as both filler and binder component. Moreover, geopolymer mortars produce significantly lower CO₂ emissions (0.133 t/m³) compared to ordinary Portland cement mortars (0.415 t/m³), highlighting their environmental advantage. These results underscore the potential of tuff-based geopolymer mortars for sustainable construction applications.